Characteristics of the Soils Supporting Quality Class I Eucalyptus tereticornis in South Bengal - Banerjee, B.; Nandi, Aparajita; Nath, S.; Banerjee, S. K. (Indian Forester, 1986)
Soil of quality class I Eucalyptus tereticornis in South Bengal have been studied for their morphological characteristics and physicochemical attributes. The soils are acidic and poor in organic matter. The sudace soils are light but clay translocation is common in most of the profiles. The chemical composition of the soils has been influenced to a great extent by drainage condition, differential transport of eroded material, leaching, translocation, redeposition of mobile soil constituents and formation and abundance of mottles. Chemical composition also indicates trends of laterisation of organic matter and break-down of parent material into free silica and sesquioxides.